2017
DOI: 10.7554/elife.23040
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent shaping of hippocampal CA1 intracellular activity in novel and familiar environments

Abstract: The hippocampus is critical for producing stable representations of familiar spaces. How these representations arise is poorly understood, largely because changes to hippocampal inputs have not been measured during spatial learning. Here, using intracellular recording, we monitored inputs and plasticity-inducing complex spikes (CSs) in CA1 neurons while mice explored novel and familiar virtual environments. Inputs driving place field spiking increased in amplitude – often suddenly – during novel environment ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
170
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(194 citation statements)
references
References 100 publications
(195 reference statements)
24
170
0
Order By: Relevance
“…The long-term stabilization of the place code for a given environment would then depend on plasticity, which could involve regenerative dendritic spikes or plateau potentials—large calcium-mediated complex spike events [13 •• ,63,71 • ]. This idea is consistent with newer research indicating that plateau potentials are not necessary for the formation of fields but contribute to their long-term stabilization [72 • ]. Variability in place cell stability seen, for example, in superficial versus deep layers could then arise from differences in single-cell biophysics that render the conditions for a plateau potential induction more or less favorable.…”
Section: Introductionsupporting
confidence: 57%
“…The long-term stabilization of the place code for a given environment would then depend on plasticity, which could involve regenerative dendritic spikes or plateau potentials—large calcium-mediated complex spike events [13 •• ,63,71 • ]. This idea is consistent with newer research indicating that plateau potentials are not necessary for the formation of fields but contribute to their long-term stabilization [72 • ]. Variability in place cell stability seen, for example, in superficial versus deep layers could then arise from differences in single-cell biophysics that render the conditions for a plateau potential induction more or less favorable.…”
Section: Introductionsupporting
confidence: 57%
“…Our findings are consistent with a model in which a new environment is associated with decreased network inhibition which then gradually recovers over the course of learning to stabilize the network, possibly via synaptic plasticity (Cohen et al, 2017;Wilson and McNaughton, 1993). We tie inhibitory suppression to learning in two ways.…”
Section: Discussionsupporting
confidence: 89%
“…Our observation are consistent with these predictions, and part of the delay period that we observed in some place fields could be due to the time required for long term potentiation to fully take effect (Hardie and Spruston, 2009; Murakoshi et al, 2011; Tigaret et al, 2016). This idea is partly supported by a recent somatic intracellular place cell recording study that found increasing sub threshold responses in novel virtual environments before somatic place field firing began (Cohen et al, 2017). …”
Section: Discussionmentioning
confidence: 85%